Neonicotinoid Pesticides Are More Toxic to Honey Bees at Lower Temperatures: Implications for Overwintering Bees - Saleem, Muhammad Shoaib; Huang, Zachary Y.; Milbrath, Meghan O. (Frontiers in Ecology and Evolution, 2020)
The honey bee (Apis mellifera) is an important pollinator and also an important test model for pesticide effects on other insect pollinators. Honey bees have been experiencing high mortality in both the US and worldwide and pesticide exposure has been identified to be one of the many stressors causing this mortality. Effects of various pesticides have been measured for multiple responses such as learning, memory performance, feeding activity, and thermoregulation. These studies were conducted at many different temperatures (11- 35°C), however, almost no studies compared toxicity of the same pesticide to bees at different temperatures. It is possible that the same pesticide might show different toxicity to honey bees at different temperatures. To reveal such potential interactions, we administered low doses of two neonicotinoid insecticides (imidacloprid and thiamethoxam) at different temperatures (35, 24 and a varying temperature) and determined their effects on honey bee survivorship. We discovered that honey bees are much more sensitive to neonicotinoid pesticides, imidacloprid and thiamethoxam, at a constant 24ºC or at a varying temperature (night at 13ºC and day at 24ºC) compared to bees at 35°C. These results suggest that honey bee colonies during winter time will be more sensitive to pesticides. Doses of neonicotinoids that are safe to colonies during summer might kill them during the winter time.